Effects of Power Allocation and User Mobility on Non-Orthogonal Multiple Access Using Successive Interference Cancellation - Niamah, Khoirun; Larasati, Solichah; Jannah, Raudhatul (Faculty of Engineering, Universitas Tanjungpura, 2021)
This research based on simulation to show impact of the power allocation on Non-Orthogonal Multiple Access (NOMA) using Successive Interference Cancellation (SIC). NOMA used superposition code (SC) on the transmitter and SIC on the receiver. NOMA has two categories power domain (PD) and code domain (CD). This research based on PD-NOMA simulated for downlink. The number of users who use the same recourse block are divided into two conditions: user with apply SIC and without SIC base on the value of channel gain from each user. Applying SC on the transmitter and SIC on the receiver will cancel of interference. Novelties of this research are the best performance of power allocation and user mobility based on parameter BER and SNR. Allocation of the power transmit based on value of channel gain every user, where user with value of channel gain is low will be allocated high power transmit, and otherwise. The best result performance of BER vs SNR used ratio power transmit 0.45 dB:0.55 dB, BER get value SNR for 17 dB and 18 dB. The best performance SNR for mobility of user with speed = 40 km/h value SNR 18 dB for BER . This research has proposed to show impact of power transmit and interference in performance NOMA.